2014
DOI: 10.1371/journal.pone.0089721
|View full text |Cite
|
Sign up to set email alerts
|

Association between Vitamin D Status and Risk of Metabolic Syndrome among Korean Postmenopausal Women

Abstract: This study aimed to investigate the association between serum levels of 25-hydroxyvitamin D [25(OH)D] and metabolic syndrome along with its associated risk factors in Korean postmenopausal women. This study was performed using data from the KNHANES 2008–2010 study and included 4,364 postmenopausal Korean women. Clinical and other objective characteristics, seasonality, and presence of metabolic syndrome with its five components were evaluated and correlated with the serum levels of 25(OH)D. Although no statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 33 publications
8
41
0
Order By: Relevance
“…To date, a statistically significant association between measured concentrations of 25(OH)D and MetS has been reported in several studies[819], though others have not found a relationship[2326]. The present study is concordant with the majority of previously published work, demonstrating a significant association between 25(OH)D and MetS, which remained after adjustment for BMI.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To date, a statistically significant association between measured concentrations of 25(OH)D and MetS has been reported in several studies[819], though others have not found a relationship[2326]. The present study is concordant with the majority of previously published work, demonstrating a significant association between 25(OH)D and MetS, which remained after adjustment for BMI.…”
Section: Discussionsupporting
confidence: 91%
“…Because of the documented relationship between BMI and concentrations of 25(OH)D, statistical models were conducted with and without BMI, and results were generally attenuated when BMI was added. As with waist circumference, the findings for triglycerides were similar to previously published work [810,1214,17,19,2325]. While the precise mechanism by which vitamin D may affect triglyceride levels is currently unknown, activity may be mediated via calcium-mediated suppression of fecal cholesterol excretion[43].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We observed significant association between hypertension and vitamin D levels. It is similar to the study done by Chon SJ et al [39] where blood pressure is negatively correlated with vitamin D levels. In our study among the lipid profiles, triglycerides and total cholesterol were significantly inversely correlated with serum levels of vitamin D. This is similar to observed by the study done by Kedam, Durgaprasr et al [33] where they showed significant inverse relation of vitamin D with triglycerides.…”
Section: Current Study and Previous Studiessupporting
confidence: 91%
“…In another study [32] of 73 European descent adults being morbidly obese (BMI ≥ 40kg/m 2 ), serum 25(OH)D levels were negatively correlated with TG (r = -0.364). Chon et al [33] suggested that Korean postmenopausal women in the highest serum 25(OH)D level showed a significant decrease in the prevalence of hypertriglyceridemia (ORs = 0.83, 95% CI = 0.71–0.97) and low HDL-cholesterol (ORs = 0.80, 95% CI = 0.69–0.93). Also, Lu et al [12] reported that among 3262 Chinese individuals aged 50–70 years, TG decreased as much as 0.10 mmol/l and HDL-cholesterol increased as much as 0.06 mmo/l per 1nmol/l increase in serum 25(OH)D levels.…”
Section: Discussionmentioning
confidence: 99%